Difference in the Effect of PNF with Trunk Exercise on Pain Reduction in Low Back Pain: Systematic Review with Meta Analysis - Samiyem, Samiyem; Ishad, Muhammad Raihan; Komalasari, Nadya Umami; Andika, Aqila Zofianesya; Ayuninggar, Lintang; Aranti, Wulan Adis; Pristianto, Arif (P3M Universitas 'Aisyiyah Surakarta, 2025)
Background: Low back pain (LBP) is a condition characterized by pain in in the lower back region. The pain felt is not a disease or a diagnosis of for a disease, it is the condition of pain syndromes in anatomical areas that experience various time variations in the occurrence of pain. Purpose: To analyze the effects of PNF and trunk exercise on pain reduction in individuals with LBP. Method: search in Pubmed, Google Scholar, and Cochrane Library databases to find and analyze related studies in the form of randomized controlled trials. Analyze related studies in the form of randomized controlled trials (RCT) without meta-analysis systematic review. The keywords used were “PNF”, “trunk exercise” and “low back pain”. Result: The results of the analysis results in this study, showed a decrease in pain in patients who received PNF by 1.70 units compared to patients with low back pain patients who were given trunk exercise (SMD = 1.70; 95% CI = 0.40 to 2.99) and the results were statistically significant (p <0.05). The result was statistically significant (p<0.00001). Heterogeneity of data the study showed I2= 95% (random effect model). Conclusion: PNF therapy is more effective than trunk exercise in reducing pain in patients with LBP.